2022
DOI: 10.1002/cam4.4575
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychosocial impact of colorectal cancer on young‐onset patients: A scoping review

Abstract: Objective:The incidence of young-onset (<50 years) colorectal cancer (CRC) has been increasing internationally. The psychosocial experience of younger cancer patients is vastly different from older patients, especially in domains such as financial toxicity, body image, and sexual dysfunction. What is unknown is the cancer type-specific experience. The aim of the current scoping review was to examine (1) the psychosocial factors and/or outcomes associated with young-onset CRC and (2) other determinants that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…Considerations relating to their stage of life and the COVID‐19 pandemic set the context for these experiences. Whereas previous work identified challenges associated with younger adults' diagnostic process, 6,27 our findings suggest the importance of perceptions of urgency both at the individual and GP level during this period.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Considerations relating to their stage of life and the COVID‐19 pandemic set the context for these experiences. Whereas previous work identified challenges associated with younger adults' diagnostic process, 6,27 our findings suggest the importance of perceptions of urgency both at the individual and GP level during this period.…”
Section: Discussioncontrasting
confidence: 89%
“…Whereas previous work identified challenges associated with younger adults' diagnostic process, 6,27…”
Section: Discussionmentioning
confidence: 95%
“…Further, this patient population may deal with different, and potentially more severe, emotional and psychological challenges than are faced by older CRC patients, especially in relation to self-image and sexual functioning 49. In our study, access to psycho-social or other support services was not noted as an issue; rather the focus of concern was self-advocacy in the take-up of such services.…”
Section: Discussionmentioning
confidence: 83%
“…In patients with EOCRC, QoL issues are particularly pronounced due to the potential for more aggressive disease, the need for intensive treatment, and the broader impact on an individual's life trajectory [9]. Studies have shown that colorectal cancer survivors experience significant challenges in physical functioning, emotional well-being, and social integration [10,11]. Moreover, the adverse effects of cancer treatments, such as chemotherapy, radiation, and surgery, can exacerbate these challenges, leading to long-term implications for patients' quality of life [12][13][14].…”
Section: Introductionmentioning
confidence: 99%